+0  
 
0
43
1
avatar

a^3+b^3=(a+b)^3-3ab(a+b) determine the sum of the ubes of two numbers if the sum of the two numbers is 4 and the product of the two numbers is 1

 Apr 17, 2020
 #1
avatar
+1

\(a^3+b^3=(a+b)^3-3ab(a+b)\) determine the sum of the cubes of two numbers if the sum of the two numbers is 4 and the product of the two numbers is 1 

let the two numbers be a and b

\(a+b=4\)

\(ab=1\)

\(a^3+b^3\) to be found.

Well,

\(a^3+b^3=(a+b)^3-3ab(a+b)\)

Substitute

\(a^3+b^3=(4)^3-3(1)(4)\)\(=64-12\)\(=52\)

.
 Apr 17, 2020

37 Online Users

avatar
avatar